The avoidable war : the dangers of a catastrophic conflict between the US and Xi Jinping's China - Rudd, Kevin 1957- (PublicAffairs, 2022)
A war between China and the US would be catastrophic, deadly, and destructive. Unfortunately, it is no longer unthinkable. The relationship between the US and China, the world’s two superpowers, is peculiarly volatile. It rests on a seismic fault—of cultural misunderstanding, historical grievance, and ideological incompatibility. No other nations are so quick to offend and be offended. Their militaries play a dangerous game of chicken, corporations steal intellectual property, intelligence satellites peer, and AI technicians plot. The capacity for either country to cross a fatal line grows daily. Kevin Rudd, a former Australian prime minister who has studied, lived in, and worked with China for more than forty years, is one of the very few people who can offer real insight into the mindsets of the leadership whose judgment will determine if a war will be fought. The Avoidable War demystifies the actions of both sides, explaining and translating them for the benefit of the other. Geopolitical disaster is still avoidable, but only if these two giants can find a way to coexist without betraying their core interests through what Rudd calls “managed strategic competition.” Should they fail, down that path lies the possibility of a war that could rewrite the future of both countries, and the world.